LOCAL CONTINGENCY PLAN FOR OIL SPILL MITIGATION AT SEA: ANECESSARY DOCUMENT THAT SHOULD BE PROVIDED TO COMBATAN EMERGENCY - M.S. Wibisono (Testing Center for Oil and Gas LEMIGAS, 2006)
The marine and or coastal environment includes its natural resources which are utilized for national development and increasing prosperity/national welfare for the Indonesian people has been clearly understood. It is necessary to be well managed in view of the 3 kinds of important and unique ecosystems which are interdependent and inter related to each other. Those marine ecosystems are as follows: 1. Mangrove ecosystems, 2. Coral reef ecosystems, 3. Sea-grass ecosystems. If one of those ecosystems degraded caused by pollution or other relevant reasons, it will decrease the carrying capacity and at last the declining productivity will prevail. This means that the degraded ecosystem will cause the imbalance in other ecosystem(s) and may contribute the outbreak of the declining productivity. Several anthropogenic activities in lands may result the impacts against one of those ecosystems stated above through the drainage system e.g. industrial effluents which do not agree with the quality standard, illegal logging, non environmental oriented development of housing complex, exchange of drainage pattern perfunctorily resulting flooding everywhere, the disposal of solid wastes/ garbage which is not well managed, and others. On the other hand the careless anthropogenic at seal coastal zone may also contribute the outbreak of the marine pollution as a result. Oil and Gas activities at sea is one of so many activities which have the environmental risks though they have been compulsory to provide the Standard Operating Procedure (SOP) particularly in self combating spill limited for their working areas. In this case the oil spill at sea which is in a huge volume of oil and happened in a sudden usually called as a disaster. The disaster which may come from one of the causal factors are among others: blow out from offshore oil-well(s), oil spill from tanker collision or grounded, disposal of dirty ballast from the vessel of which the captain breaks the ratified International Conventions, and explosion of storage tank(s) at the coastal zone. All type of oil spill at sea will give the negative impacts to the most sensitive locations. Such of those are locations in which the biota communities are still in a succession stage, or the certain locations in terms of economical potency and or natural resources and all at once facing the pollution risks, since such loca- tions are relatively close to the oil & gas operational activities, for example: a. Ponds/fish ponds (tambaks) or tourist resorts or mangrove forests or seaweed aquacultures which are relatively close to the navigational tanker route. b. Protected (preservation/conservation) areas of which the positions are relatively close to the oil & gas operational activities. Several short notes are presented in this paper to obtain the illustration of the spill at sea.The accident of TORREY CANYON happened in March 1967 spilled the Kuwait crude as much as 118.000 tons in the vicinity of Santa Barbara. But the larger spill in the world derived from the ship AMOCO CADIZ happened in 1978 polluted the English-channel. Eight years later the disaster was happened again where several storage tanks exploded and caught on fire resulting 8 million litres of crude oil spilled out and polluted the coastal zone of the Panama Bay. In 1996 a tanker was grounded and trapped in the snowy/icy seawater and stormy of the Alaskan Sea where the oil spill was very difficult to mitigate in such condition. In Asian region there was a VLCC KANCHENJUNGA (+ 270.000 DWT) grounded on control marine pollution and the act damaging the marine environment in the certain limits of authority. The aim of this paper is to obtain some positive responses from the local government level (frovincials) which having the risks of oil pollution to provide the LCP document, since they are close to the oil and gas operational activities or facing the tanker's lane.